Building an educative community for early childhood development - Rudolph, Norma (My University, 2014)
This emancipatory action research project, undertaken in South Africa between 1995 and 1999, responds to the challenge of engaging a wide variety of Early Childhood Development (ECO) role-players in policy debate and development. Through cycles of action and reflection, a model for building an ECD educative community, using the case method and Zeichner and Liston’s four traditions of reform in teacher development, is proposed and tested. New policy seeks to replace the inherited inequitable system of ECD provisioning with a multi-service approach that supports families and communities in meeting the basic needs of young children. Emancipatory action research has been chosen for its potential to stimulate critical reflection that can deliver political and practical action. Established perspectives and practice constitute major obstacles to co-operation within and across different spheres of government and between government and non-government role-players. The model for dialogue enables all stakeholders in the life of the child to reach a shared understanding of what is meant by quality in ECD, by reflecting in groups on their current practice in the light of a theoretical framework. The model was developed through two similar series of workshop, in the Northern Province in 1995 and Gauteng in 1997. A dialectical relationship exists between the action research project and the national and provincial policy development process. Experience gained in xhe two series of workshops informed the conceptualisation and development of Impilo, which is a series of linked ECD pilot projects that expand the scope and scale of the model to include all ECD role-players in Gauteng. Eighteen Gauteng Department of Education ECD district forums are the primary location for dialogue and the educative community includes other provincial departments, local government, ECD practitioners, community groups and families. On-going experience in participating Impilo pilot sites provides the focus for linking caring and reason to reflection through dialogue. The primary product of the dissertation is the research design for the evaluation of Impilo that is intended to complement the national ECD research. The effectiveness of the model for building an educative community is already evident in the ECD partnerships forged within and beyond Impilo and the basic principles of the model have been adapted for different ECD contexts. The strategies for curbing domination have been most effective. Theoretical frameworks have assisted people in moving beyond their current system of beliefs to engage with other perspectives. Helping participants reflect on their attitudes and actions has provided skills that can easily be transferred into other operational situations. This model for enabling dialogue is now supported by the broad provincial consultative ECD policy development process and preparation of provincial ECD Green Paper, which proposes a new single, comprehensive system of registering, monitoring and subsidising services that overcome hardships without impeding development. The proposed webs of ECD services provide a mechanism for linking implementation, research, policy development and advocacy.